Cannabis sativa L. extract and cannabidiol inhibit in vitro mediators of skin inflammation and wound injury. (27th June 2019) - Sangiovanni, Enrico; Fumagalli, Marco; Pacchetti, Barbara; Piazza, Stefano; Magnavacca, Andrea; Khalilpour, Saba; Melzi, Gloria; Martinelli, Giulia; Dell'Agli, Mario
Abstract : Skin inflammatory diseases result from complex events that include dysregulation and abnormal expression of inflammatory mediators or their receptors in skin cells. The present study investigates the potential effect of a Cannabis sativa L. ethanolic extract standardized in cannabidiol as antiinflammatory agent in the skin, unraveling the molecular mechanisms in human keratinocytes and fibroblasts. The extract inhibited the release of mediators of inflammation involved in wound healing and inflammatory processes occurring in the skin. The mode of action involved the impairment of the nuclear factor‐kappa B (NF‐κB) pathway since the extract counteracted the tumor necrosis factor‐alpha‐induced NF‐κB‐driven transcription in both skin cell lines. Cannabis extract and cannabidiol showed different effects on the release of interleukin‐8 and vascular endothelial growth factor, which are both mediators whose genes are dependent on NF‐κB. The effect of cannabidiol on the NF‐κB pathway and metalloproteinase‐9 (MMP‐9) release paralleled the effect of the extract thus making cannabidiol the major contributor to the effect observed. Down‐regulation of genes involved in wound healing and skin inflammation was at least in part due to the presence of cannabidiol. Our findings provide new insights into the potential effect of Cannabis extracts against inflammation‐based skin diseases.